2006
DOI: 10.1108/00907320610716431
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating to connect global citizenship, information literacy, and lifelong learning in the global studies classroom

Abstract: Purpose -This paper critically examines the concepts of lifelong learning, information literacy, and global citizenship, making explicit connections among them via theories of social capital. It then presents a model of librarian-faculty collaboration that relies upon information literacy as a framework for fostering lifelong learning and global citizenship.Design/methodology/approach -The paper begins with a theoretical analysis of lifelong learning, information literacy, global citizenship, and social capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
0
20
0
3
Order By: Relevance
“…In particular, liaison librarians actively promote incorporating information literacy skills within courses. Many articles have shown that it is these initiatives, built into course assignments, that permit students to develop an understanding of information literacy (Adler 2003;Buchanan, Luck, and Jones 2002;Ducas and Michaud-Oystryk 2003;Julien and Given 2003;Lindstrom and Shonrock 2006;Owusu-Ansah 2007;Stevens and Campbell 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In particular, liaison librarians actively promote incorporating information literacy skills within courses. Many articles have shown that it is these initiatives, built into course assignments, that permit students to develop an understanding of information literacy (Adler 2003;Buchanan, Luck, and Jones 2002;Ducas and Michaud-Oystryk 2003;Julien and Given 2003;Lindstrom and Shonrock 2006;Owusu-Ansah 2007;Stevens and Campbell 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Educators in the field of technical communication and in many other fields are focusing a great deal of attention on the need to prepare students to function in the global marketplace [5,7,8,9,10]. Students must be prepared to work in a multicultural environment.…”
mentioning
confidence: 99%
“…Stevens and Campbell also believed the goal of heightening the global awareness and competency of the students was achieved. For many students, their research into resource conflicts became very personal and they appeared to internalize how they were connected to the world and how their consumption of resources affected other people around the globe (Stevens and Campbell 2008). were capped at fifteen students to keep the interaction with foreign partners manageable.…”
Section: Literature Reviewmentioning
confidence: 99%